An Investigatory Project of Dried Leaves as an Alternative Component for Paper Production: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In this study, it turns out that we, too, require papers before we can produce any. They areregarded as the fiber required for paper manufacture. As trees naturally contain fibers,producing paper using them is easier. But, since paper is required everywhere, tree cuttingbecomes a problem rather than a solution to the problem of a lack of paper. Because trees arebeing taken down for paper production, catastrophes like floods and deforestation occur. Wewill use paper as fiber since there is already too much paper trash in the world, which isbeginning to pose a threat to the environment. There are three issues that will be discussed inthis study: tree cutting, paper waste, and the problem of dried leaves. These problems arebigger than what everyone assumes they are.It indicates that there is a significant difference between and among the assessments of twogroups of respondents in terms of ingredients. Procedural methodology, Durability, andUsability. The overall weighted mean of the science teachers is 3.51, while the studentsacquired 3.11. The variance of Science teachers was 0.136, while the Students acquired0.0972. The T-critical value is 2.306 while the t computed is 2.306. Therefore, it accepts Ho. Itindicates that there is no significant difference between the tree-produced paper and leaf-produced paper in terms of ingredients. Procedural methodology, durability, and Usability.For further enhancement and improvement of the project, the ensuing discussions and therecommendations proposed are as follows: use more paper than the dried leaves. Therespondents also recommended using thickeners, like cornstarch syrup, for the moldingprocess.
Keywords: Manufacturing engineering